2006
DOI: 10.1517/13543784.15.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Current therapeutic uses of lenalidomide in multiple myeloma

Abstract: Thalidomide has demonstrated a broad spectrum of pharmacological and immunological effects, with potential therapeutic applications that span a wide spectrum of diseases: cancer and related conditions; infectious diseases; autoimmune diseases; dermatological diseases; and other disorders such as sarcoidosis, macular degeneration and diabetic retinopathy. Immunomodulatory derivative lenalidomide has more potent antitumour and anti-inflammatory effects. The molecular mechanisms of antitumour activity of lenalido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 73 publications
0
20
0
Order By: Relevance
“…An arguably faster path to development is to reposition established drugs as anticancer agents. Successful examples of this approach include cyclooxygenase-2 inhibitors, which are FDA-approved anti-inflammatory drugs that are approved for cancer chemoprevention in familial adenomatous polyposis patients, and lenalidomide, an analogue of thalidomide, which was originally marketed for morning sickness that is now approved for therapy of myelodysplastic syndromes (24). Other approved drugs that are currently under investigation as anticancer agents include the oral hypoglycemic rosiglitazone, the immunosuppressant rapamycin, and the birth control hormone medroxyprogesterone acetate.…”
Section: Discussionmentioning
confidence: 99%
“…An arguably faster path to development is to reposition established drugs as anticancer agents. Successful examples of this approach include cyclooxygenase-2 inhibitors, which are FDA-approved anti-inflammatory drugs that are approved for cancer chemoprevention in familial adenomatous polyposis patients, and lenalidomide, an analogue of thalidomide, which was originally marketed for morning sickness that is now approved for therapy of myelodysplastic syndromes (24). Other approved drugs that are currently under investigation as anticancer agents include the oral hypoglycemic rosiglitazone, the immunosuppressant rapamycin, and the birth control hormone medroxyprogesterone acetate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent data has suggested that immunomodulatory drugs can also favorably influence the activity of dendritic cells in this setting (56). The data supporting the immunomodulatory role of these agents, including thalidomide and lenalidomide, have been derived preclinically and now most recently clinically (10,57). Therefore, a combination therapy using 1D09C3 in association with immunomodulatory drugs might represent a compelling avenue.…”
Section: Discussionmentioning
confidence: 99%
“…LEN appears to have direct and indirect effects, including the ability to inhibit cell growth and survival, induce apoptosis, inhibit adhesion to the host microenvironment, inhibit angiogenesis, and augment immune cell activity. 18 It has been hypothesized that some or all of these effects might also influence keratinocytes in patients receiving LEN and contribute to rash development. 8 As such, some authors attribute LEN-related rash to its direct antitumor effects, others to its indirect immunomodulatory effects.…”
Section: Physiology Of Len-related Rashmentioning
confidence: 99%